Magnetothermoelectric properties of single-crystal wires and films based on Bi–3at%Sb - Nikolaeva, Albina (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2019)
Results of a study of the magnetothermoelectric properties and the Shubnikov–de Haas effect in single-crystal wires of various diameters and films based on Bi1–xSbx semimetal alloys have been described. According to the Shubnikov–de Haas oscillations, it has been calculated that the overlap of the L and T bands in the Bi–3at%Sb semimetal wires decreases more than twofold owing to an increase in the antimony concentration. Thermoelectric gap E, the dependence of the gap on wire diameter d, and the temperature dependence of power factor 2(T) as a function of diameter and magnetic field have been calculated. It has been found that a decrease in wire diameter d leads to a semimetal–semiconductor transition at d < 1.2 m, which is more than an order of magnitude higher than in pure Bi wires and 1.5 times higher than in wires of Bi–2at%Sb alloys. It has been shown that thermal gap E increases with decreasing wire diameter d in accordance with a law close to 1/d, which is consistent with theoretical calculations based on the occurrence of the quantum size effect in semimetals. A switching effect in the magnetothermopower has been found; the dependence of this effect on wire diameter d and temperature has been determined. It has been shown that, in a weak magnetic field, the magnetothermopower anisotropy in Bi–3at%Sb wires and films increases with decreasing temperature; this feature can be used in anisotropic thermoelectric energy converters.